SCIENTIFIC RESEARCH ON THE STUDY OF THE TOPOGRAPHY OF THE ANCIENT CITY OF THE FERGHANA VALLEY (Scientific journal of the Fergana State University, 2023)
The article covers the historiography of the ancient Ferghana Valley. The beginning of the millennium is considered a period of great migrations in the Eurasian region. In Chinese written sources, the Huns, Guns, or Yuechi continued to move from east to west or vice versa. The great migrations, the intermingling of peoples and peoples, will lead to great changes in the cultural world and geopolitics. Of course, such worldly changes did not bypass the Fergana Valley. Until now, the history of this period, its culture, is interpreted only on the basis of archaeological materials. The study of the culture of nomadic herders in Central Asia is mainly based on research conducted in burial mounds. As some of the uncovered ancient city ruins have been uncovered to one degree or another, the historical topography of the cities still cannot be fully revealed. Although these studies conducted until 2000s were a natural situation in their time, these conclusions are rare today. Because as a result of analyzing animal bones, plant remains and seeds, the role of natural factors in the crisis of climate change is a serious issue in front of science. In the reconstruction of ancient history, the origin of communities and peoples, genetic engineering is being restored based on modern anthropological analysis, and it is possible to trace the complete family tree of their migration issues.